Overview: Why and How Does Reflection Matter in Workplace Learning?. Issue 3 (August 2020) - Faller, Pierre; Lundgren, Henriette; Marsick, Victoria
The Problem: While reflection is central to adult learning processes and theories, its meaning and definitions vary. Authors approach reflection from different perspectives and assumptions. The Solution: This article is a conceptual map to guide the reader through key definitions and perspectives discussed in upcoming articles. We provide a compass for reflection, critical reflection, reflective practice, and how these terms apply to learning from experience, meaning-making, and action in the workplace. We also show how different perspectives or lenses can impact a human resource development (HRD) practitioner's approach to reflection and present several studies looking at reflection and reflective practices. The Stakeholders: This article should help HRD practitioners and others engaged in supporting workplace learning to gain clarity about how to conceptualize reflection and reflective practices and become familiar with the different ways reflection is understood by authors of upcoming articles.